Quality of service study in synchronized time-triggered aerial networks - Tariq, Nahman; Petrunin, Ivan; Al-Rubaye, Saba; Tsourdos, Antonios; Zischka, Wolfram (IEEE, 2020)
Unmanned aerial vehicles (UAVs) have shown tremendous potential in both military and civilian applications, for example, in delivery services, search and rescue, and surveillance. Currently, UAVs can perform several tasks while in flight. UAVs have real-time systems with limited capability for time-triggered synchronization, which impose synchronization limitations for their platforms. Additionally, there is no time-triggered synchronization between the UAVs and the ground station. One of the requirements for a reliable communication links between a UAV and a ground station is the need for synchronization using Global Navigation Satellite System (GNSS) in a time-triggered network. However, the information exchange between UAV and ground station lacks the time-triggered abilities. In this context, GNSS time can be used as an external source to allow UAV performing tasks connected to the ground station with time-stamped messages. In this paper, we investigate the capability of GNSS as an external time source for the time-triggered network to achieve high quality of service (QoS) of a communication link between the ground station and UAV. Simulations analysis was conducted to evaluate the overall system performance, which gives a better understanding of performance of a time-triggered wired and wireless network
Keywords: Virtual Links; Quality of Service; System of Systems; Network; UAVs; Time-Triggered